2022
DOI: 10.3171/2021.10.focvid21190
|View full text |Cite
|
Sign up to set email alerts
|

Use of an exoscope for enhanced visualization of a Schwab grade 5 osteotomy to correct kyphotic deformity

Abstract: The development of the 3D exoscope has advanced intraoperative visualization by providing access to visual corridors that were previously difficult to obtain or maintain with traditional operating microscopes. Favorable ergonomics, maneuverability, and increased potential for instruction provide utility in a large range of procedures. Here, the authors demonstrate the exoscope system in a patient with progressive thoracolumbar junctional kyphosis with bony retropulsion of a T12–L1 fracture requiring a Schwab g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Giorgi et al demonstrated in a series of patients with thoracolumbar fractures with spinal cord compression a crucial improvement of the user-friendliness and visualization in lateral thoracolumbar procedures through the possibility to simply shift between microscopic and macroscopic vision without moving the exoscope and without blocking the deep surgical field 13 . Although we experienced some surgical time prolongation in the first two lateral cases, we quickly established an OR setup for all spine procedures based on the patient positioning, which diminished the setup conflicts and allowed a better positioning of the C-Arm.The exoscopic systems already demonstrated satisfying magnification and stereoscopic vision even in more challenging and extensive deformity correction procedures 14 . Still the major advantages, which we also observed in our study, are the improvement of 3D depth perception and magnification in minimally invasive procedures like the classical anterior cervical approach and the lateral thoracolumbar minithoracotomy or the retroperitoneal approach.…”
Section: Discussionmentioning
confidence: 99%
“…Giorgi et al demonstrated in a series of patients with thoracolumbar fractures with spinal cord compression a crucial improvement of the user-friendliness and visualization in lateral thoracolumbar procedures through the possibility to simply shift between microscopic and macroscopic vision without moving the exoscope and without blocking the deep surgical field 13 . Although we experienced some surgical time prolongation in the first two lateral cases, we quickly established an OR setup for all spine procedures based on the patient positioning, which diminished the setup conflicts and allowed a better positioning of the C-Arm.The exoscopic systems already demonstrated satisfying magnification and stereoscopic vision even in more challenging and extensive deformity correction procedures 14 . Still the major advantages, which we also observed in our study, are the improvement of 3D depth perception and magnification in minimally invasive procedures like the classical anterior cervical approach and the lateral thoracolumbar minithoracotomy or the retroperitoneal approach.…”
Section: Discussionmentioning
confidence: 99%